A Linear and Non-Linear Causality Analysis between Military Expenditures and External Debt in NATO Member Countries (European Journal of Marketing and Economics, 2024)
This paper investigates the causal nexus between military expenditure and external debt across NATO countries from 1960 to 2015 using both linear and non-linear Granger causality frameworks. Its primary innovation lies in the empirical application of the Francis et al. (2010) non-linear test, marking the first known study to utilize this methodology for exploring complex, non-linear dependencies between defense spending and national debt. The empirical results reveal distinct patterns: linear causal relationships are evident in Greece, Italy, the UK, and the USA, while significant non-linearities characterize the dynamics in Turkey and the USA. By identifying these diverse causal directions, the study offers a more sophisticated understanding of how defense budgets impact fiscal stability. Ultimately, these findings provide essential guidance for regulators and decision-makers, equipping them with the evidence needed to balance national security requirements with sustainable debt management strategies within the NATO alliance.
Keywords: military expenditures, external debt, NATO countries